SIMULIIDAE DE CHILE: LISTA DE ESPECIES Y SU DISTRIBUCION GEOGRAFICA. (DIPTERA: SIMULIIDAE) - Henry, Abel (Acta Entomológica Chilena, 2022)
The 46 species of Simuliidae known from Chile are listed. For each species are given: original citation, synonyms, geographical distribution and references. New localities records and blood-sucking habits species are indicated.